Transformasi Lembaga Pendidikan Islam Indonesia di Era Artificial Intelligence (AI): Analisis Filosofis terhadap Perubahan Paradigma Pendidikan - Hakiki, Darul Qutni; Ilham Kamaruddin; Hamdan Saleh; Ahsan Hakim (PARADIGMA: JURNAL PEMIKIRAN DAN PENELITIAN PENDIDIKAN, 2026)
This study aims to analyze the transformation of Islamic educational institutions in the era of Artificial Intelligence (AI) through a philosophical approach encompassing ontological, epistemological, and axiological dimensions. This research employs a qualitative method with a library research design, analyzing relevant academic literature on AI and Islamic education. The findings reveal that AI does not merely introduce technical changes but also generates fundamental implications for the paradigm of Islamic education. Ontologically, humans possess a spiritual dimension and moral responsibility as khalifah, whereas AI is a material artifact lacking consciousness and existential capacity. Epistemologically, AI knowledge is computational and data-driven, while Islamic education views knowledge as an integration of revelation, reason, and empirical experience, encompassing meaning and value. Axiologically, AI is not value-neutral but reflects instrumental goals, whereas Islamic education is oriented toward moral formation and transcendental objectives. The study implies that the integration of AI in Islamic education must be positioned as a means (wasilah), not an end (ghayah). Therefore, the transformation of Islamic educational institutions should reinforce the principles of tawhid, adab, and moral responsibility, ensuring that technological advancement does not shift the ultimate goal of education, which is the formation of knowledgeable, faithful, and virtuous individuals.